2022
DOI: 10.1007/s43545-022-00540-3
|View full text |Cite
|
Sign up to set email alerts
|

White prevalence and White preference in children’s books in China

Abstract: The study of the ethnicity of authors, illustrators, and characters in children’s literature is important for understanding the ethnic normativity messages that children receive through books. However, ethnic representation in children’s books has rarely been studied in Asian countries. The present study examined the ethnic representation of authors, illustrators, and characters of books for young children that (1) won awards, or (2) were in the annual sales ranks in one of the most popular online book stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This was reflected for example by Chinese children's portrait drawing of human figures which were made to look like White people (Wang, 2018). In addition, a study of racial representation in books for young children in China revealed a dominant representation of White characters and a preference for light skin tone in East Asian characters in illustrations (Yang et al., 2022). Advertisements and magazines in China showcase many White models (Jung, 2018), and children walking seeing those might be sensitive to this preference for whiteness (Chan et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This was reflected for example by Chinese children's portrait drawing of human figures which were made to look like White people (Wang, 2018). In addition, a study of racial representation in books for young children in China revealed a dominant representation of White characters and a preference for light skin tone in East Asian characters in illustrations (Yang et al., 2022). Advertisements and magazines in China showcase many White models (Jung, 2018), and children walking seeing those might be sensitive to this preference for whiteness (Chan et al., 2012).…”
Section: Introductionmentioning
confidence: 99%